Bioconjugação de nanopartículas de ouro em peptídeos sintéticos baseados em sequências imunogênicas de NS1 oriundas dos vírus Dengue tipo I, II, III, e IV - Costa, Danilo Soares (2017)
Recently, nanocarriers made of synthetic peptides conjugated with gold nanoparticles (AuNP) has been considered an efficient platform for immunogen delivery and production of antibodies. Although metal nanovaccines surpass issues arising from traditional vaccination with live attenuated pathogens or inactivated pathogens, the application and stability of nanobiointerfaces in biological systems remains a questionable gap related to the method for conjugation. This work describes bioconjugation via electrostatic attraction and covalent bound of immunogenic peptides on the surface of gold nanosphere and evaluates their stability in a large range of salt concentrations and pH. Protean® software predicted the immunogenic sequences in non-structural protein 1 (NS1) from the 04 dengue virus (DENV) serotypes, then synthesized in solid phase and characterized with HPLC and ICP-MS. Techniques such as UV-vis, Fluorimetry, FTIR, Raman, Zeta Potential and DLS, as well as TEM were employed to characterize both electrostatic and covalent approaches before and after bioconjugation. The interaction between peptide derived from DENV1 NS1 with AuNP demonstrated better efficiency in the connection process and in the stability of the conjugated nanbiomaterial for both approaches. Therefore, these data open new perspectives for the use of nanobioconjugates with immunogenic peptides as platforms for drug / immunogen delivery.